Assessment in Mathematics Education: Between Time, Technologies and Pedagogical Choices - Manya Maneva (Педагогически форум, 2025)
The article examines assessment in mathematics education as a key component of pedagogical practice, situated in the context of the contradiction between the requirements for standardization, time restrictions and technical resources and the need for professional autonomy. Through an empirical study based on a quantitative analysis of data collected from 188 mathematics teachers, dominant patterns of behavior in the construction, application and interpretation of assessment tools in lower secondary and upper secondary education are identified. The results outline significant dependencies between professional experience, the level of qualification held and the engagement with analytical activities related to the reliability and validity of test tasks. The predominant use of combined assessment formats is noted, which demonstrates a desire to integrate objective and productive measures of knowledge and skills. Despite the expanding access to digital tools, the practice is still dominated by paper media, especially at lower educational levels. The analysis reveals systemic limitations – lack of time to provide feedback, difficulties in assessing high cognitive skills and uneven support across school contexts. The study argues for the need for targeted professional development policies, infrastructural provision and methodological support to ensure sustainable and pedagogically effective implementation of modern approaches to mathematics assessment.